Physical unclonable functional material based on diamond particles as well as preparation method and application of physical unclonable functional material

CN119256065APending Publication Date: 2025-01-03VERSITECH LTD +1

Patent Information

Application Number
CN202380042648.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-15
Filing Date
2023-05-23
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Existing optical PUF labels have poor stability in complex environments, and most are produced in solutions that are incompatible with microelectronic devices, making it difficult to achieve large-scale compatible production. They are also vulnerable to machine learning attacks and have insufficient security.

Method used

Nano-diamond particles are prepared using a salt-assisted air oxidation high-pressure and high-temperature method. Diamond particles with silicon vacancy color centers are heterogeneously grown on a single crystal silicon substrate. Ultra-stable and adjustable silicon vacancy color centers are grown through chemical vapor deposition. The electroluminescence and light scattering signals form a physically unclonable functional material based on diamond particles.

Benefits of technology

Realized physical unclonable functional materials with high stability, multi-mode encryption capabilities and robustness in harsh environments, suitable for anti-counterfeiting systems, capable of large-scale commercial customization in electronic components and other fields, improving the security of anti-counterfeiting labels and compatibility.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119256065A_ABST
    Figure CN119256065A_ABST
Patent Text Reader

Abstract

The invention provides a physical unclonable functional material based on diamond particles and a preparation method and application thereof. The physical unclonable functional material comprises a monocrystalline silicon substrate and diamond particles which grow on the monocrystalline silicon substrate in situ and have silicon vacancy color centers. The preparation of diamond particles on a silicon substrate is a random process, which is a key requirement for manufacturing a physical unclonable function label. According to the method, the scattered spectrum of the diamond particles and the morphological characteristics and spatial position relation of the diamond particles are used as the fingerprint information of the diamond physical unclonable functional material. Due to the extremely heat resistance, mechanical stability, chemical stability and light stability of the diamond material, the high-robustness label can meet the requirements of many practical applications in various environments, and has practical commercial value in huge anti-counterfeiting markets such as electronic elements, medicine packaging, vehicles and luxury.
Need to check novelty before this filing date? Find Prior Art

Description

Physically unclonable functional materials based on diamond particles and preparation methods and applications thereof Technical Field

[0001] The invention relates to a physically unclonable functional material based on diamond particles, a preparation method and an application thereof. Background Art

[0002] Counterfeiting is a growing global problem, prevalent in the manufacturing of a wide range of products, from everyday consumer goods to pharmaceuticals and high-tech gadgets, severely impacting financial security, national security, and even threatening human health. To date, various anti-counterfeiting strategies, including watermarks, holograms, barcodes, and QR codes, have been developed to prevent counterfeiting. However, most of these labels are manufactured using repeatable, deterministic processes, making the encoded information vulnerable to counterfeiting attacks by third parties with relevant expertise. Therefore, to address the growing global counterfeiting problem, the design and development of unbreakable anti-counterfeiting labels is urgently needed.

[0003] One promising approach that has recently garnered attention involves the use of security tags with physically unclonable functions (PUFs). A PUF is a hardware security technology that generates a unique and random response signal whenever it receives an excitation signal. Because PUFs rely on the uniqueness and randomness of their physical microstructure, they are unpredictable and uncontrollable, making it virtually impossible to copy or clone the hardware structure. To date, a variety of materials (e.g., photonic crystals, metal nanoparticles, semiconductor nanoparticles, DNA nanostructures, hydrogels, upconversion nanoparticles, etc.) and fabrication methods (e.g., drop coating, spin coating, self-assembly, inkjet printing, etc.) have been developed to implement PUFs for anti-counterfeiting.

[0004] Currently, PUFs primarily fall into two categories: optical and electrical. Electrical PUFs rely on simple electrical signals for input and output, making them vulnerable to machine learning attacks and the ability to model and replicate stimulus responses, resulting in poor security. Optical PUFs have attracted increasing attention due to the excellent optical properties of the luminescent components they employ. This is because their optical characteristics, such as fluorescence color, intensity, and lifetime, can be manipulated across multiple dimensions, resulting in inherent randomness, controllability, and diversity. For example, the luminescence of these components (such as quantum dots, perovskites, polymer dots, upconversion nanoparticles, plasmonic nanoparticles, phosphors, and lanthanide complexes) can be modulated (excited, quenched, or tuned) by a range of external stimuli (light, heat, chemicals, and mechanical forces), making them ideal materials for advanced cryptography. Despite their undeniable importance, most optical PUFs exhibit unsatisfactory stability in complex environments (e.g., high temperature, strong acids, strong bases, ultraviolet light, mechanical scratching, etc.). Furthermore, most are produced in solution using wet chemical synthesis methods, which can be incompatible with microelectronic devices and may adversely affect their primary product functionality. Therefore, the development of new reliable PUF tags with compatible large-scale production processes is expected to promote the development and practical application of next-generation anti-counterfeiting technologies.

[0005] In recent years, diamond has been widely used in various fields due to its unique chemical inertness, excellent mechanical strength, and high-temperature stability. Furthermore, various luminescent color centers within diamond crystals, such as nitrogen vacancy (NV) and silicon vacancy (SiV) color centers, have attracted widespread attention in a variety of applications due to their unique optical and spectral properties. Furthermore, the surface chemistry, shape, and geometry of diamond materials can be regulated through their synthesis methods (e.g., high pressure, high temperature, and chemical vapor deposition techniques) and other post-processing methods (e.g., surface modification, reactive ion etching, and air oxidation). Therefore, the optical properties of color centers embedded within diamond crystals are sensitive to their surface chemistry, structure, and shape, making them difficult to accurately clone or counterfeit. In particular, SiV color centers exhibit near-infrared (NIR) emission near 737 nm, which is invisible to the naked eye and can be captured by most commercial cameras, thus simplifying the distinction between confidential information and interference. Therefore, NIR-emitting color centers such as SiV in diamond hold great potential for optical PUF tags.

[0006] US10685199B2 proposes using the orientation information of nitrogen-vacancy color centers in nanodiamonds to generate a unique anti-counterfeiting code. The preparation method involves coating a suspension containing diamond particles on the surface of an object, or incorporating the suspension into a material and forming the object from that material. This technique requires advanced microscopy to read the orientation of the nitrogen-vacancy color centers in the nanodiamonds. Based on this technology, nanodiamonds containing nitrogen-vacancy color centers can be used as anti-counterfeiting materials for advanced security services.

[0007] In addition, some scholars have proposed using nitrogen vacancies in diamond as a PUF signal readout analysis technology, but have not taught the use of diamond particles themselves as the construction material of PUF (J.Appl.Phys.2020,127,203904,PUFs enabled by an array of randomly magnetized micrometer-sized ferromagnetic bars(micromagnets),the magnetic polarity of each micromagnet was analyzed by NV centers in diamond).

[0008] With the development of chemical vapor deposition (CVD) and controlled doping technology, it has become possible to grow high-quality, large-area diamond particles containing different color centers on various substrates at a relatively low cost. The position, size, and shape of diamond particles grown by CVD are highly dependent on various parameters of the CVD technology, such as the seed, nucleation, and growth process. These are highly random (non-deterministic) processes, which are also a key requirement for the manufacture of PUF tags. However, their robustness in complex working environments must be continuously improved to adapt to practical applications.

[0009] Summary of the Invention

[0010] Therefore, the object of the present invention is to provide a diamond particle containing silicon vacancy color centers, so as to be used as a robust physically unclonable functional material for an optical anti-counterfeiting system.

[0011] The inventors unexpectedly discovered that using nanodiamonds prepared by salt-assisted air oxidation, high-pressure, high-temperature (HPHT) as seeds for chemical vapor deposition (CVD), heterogeneously grown diamond particles on a silicon substrate can emit ultrastable, intense, and tunable signals: 1) photoluminescence (PL) from silicon vacancy color centers; and 2) light scattering. The inventors realized that the PL intensity of silicon vacancy color centers and the light scattering patterns and spectra of diamond particles can contribute to the development of multidimensional PUF tags with large encoding capacity. Furthermore, the inventors demonstrated that this diamond-based PUF material exhibits exceptional stability in harsh chemical environments, high temperatures, mechanical wear, and UV irradiation. The material provided by this invention exhibits extremely high randomness, multimodal encryption capabilities, and excellent robustness, demonstrating great potential for use as anti-counterfeiting labels in various fields.

[0012] Based on the above findings, a first aspect of the present invention provides a physically unclonable functional material based on diamond particles, comprising: a single crystal silicon substrate and diamond particles having silicon vacancy color centers in-situ grown thereon.

[0013] In a preferred embodiment of the present invention, the diamond particles having silicon vacancy color centers are grown on the single crystal silicon substrate by chemical vapor deposition. Preferably, the chemical vapor deposition method uses nanodiamonds that have been subjected to salt-assisted air oxidation as chemical vapor deposition seeds.

[0014] According to the physically unclonable functional material based on diamond particles provided by the present invention, the salt-assisted air oxidation treatment may include mixing nanodiamonds with a soluble salt and heating them in air at 200-900°C for 1 minute to 24 hours, wherein the soluble salt is preferably sodium chloride; preferably, the mass ratio of the nanodiamonds to the soluble salt is 1:0.1-10.

[0015] According to the physically unclonable functional material provided by the present invention, the particle size of the diamond particles may be 50 to 100,000 nm, preferably 100 to 10,000 nm.

[0016] Wherein, the particle size of the nanodiamond used as the chemical vapor deposition seed can be 1 to 500 nm, preferably 5 to 100 nm.

[0017] According to the physically unclonable functional material of the particles provided by the present invention, the growth surface of the single crystal silicon substrate is a (100) crystal plane.

[0018] According to the physically unclonable functional material of the present invention, the coverage of the diamond particles on the surface of the single crystal silicon substrate can be 0.1% to 100%, preferably 10 to 50%.

[0019] Figure 1 shows the structure (a) and energy levels (b) of a silicon vacancy color center in a diamond unit cell, a physically unclonable functional material based on diamond microparticles of the present invention. The silicon vacancy color center in the diamond microparticle consists of an interstitial silicon atom and two adjacent vacancies in the diamond lattice. At low temperatures, the energy levels of the silicon vacancy color center include a split ground state and a split excited state. The separation between the two split energy levels of the ground state is approximately 50 GHz, and the separation between the two split energy levels of the excited state is approximately 250 GHz. There are four allowed optical transitions.

[0020] A second aspect of the present invention provides a method for preparing a physically unclonable functional material based on diamond particles, the method comprising:

[0021] (1) salt-assisted air oxidation treatment of nanodiamonds;

[0022] (2) preparing the treated nanodiamond into a seed suspension;

[0023] (3) Spin-coating the seed crystal suspension onto the surface of a single-crystal silicon substrate to form seed crystals, and then growing diamond particles having silicon vacancy color centers by chemical vapor deposition.

[0024] According to the preparation method provided by the present invention, the salt-assisted air oxidation treatment may include mixing the nanodiamond with a soluble salt and heating it in air at 200-900° C. for 1 minute to 24 hours, wherein the soluble salt is preferably sodium chloride.

[0025] According to the preparation method provided by the present invention, the seed crystal suspension can use dimethyl sulfoxide, anhydrous ethanol, acetone, water or a mixture thereof as a dispersion solvent.

[0026] According to the preparation method provided by the present invention, step (3) includes treating the single crystal silicon substrate with hydrogen plasma before growing diamond particles, and the preferred treatment conditions are: power of 100 to 2000 W, chamber pressure of 0.1 to 100 torr, hydrogen (H2) gas flow rate of 5 to 1000 sccm, and treatment time of 1 to 60 minutes.

[0027] According to the preparation method provided by the present invention, the chemical vapor deposition growth conditions in step (3) include: spin coating the seed suspension on the surface of the pretreated silicon substrate (spin coating parameters: 100-5000 r / min, adding 1-10 drops within 5-60 seconds, then increasing the speed to 1000-10000 r / min, spinning for 10-300 seconds and drying), and repeating this process 1-30 times. Subsequently, the silicon substrate spin-coated with the diamond seed is placed in a chemical vapor deposition device to deposit and grow diamond particles, the device microwave power is 500-5000 W, the chamber pressure is 0.1-100 torr, the growth temperature is 400-1000° C., the hydrogen gas flow rate is 100-1000 sccm, the methane (CH4) gas flow rate is 1-100 sccm, and the growth time is 10-120 minutes.

[0028] According to the preparation method provided by the present invention, the preparation method may further include step (4) heating the generated diamond particles in air to increase the photoluminescence intensity of the silicon vacancy color center. The inventors of the present invention unexpectedly discovered during experiments that the photoluminescence intensity of the silicon vacancy color center can be modulated by oxidizing the generated diamond particles in air for different periods of time. For example, the experiment observed that during cumulative heating at 600°C in air for 0, 15, 30, 45, and 60 minutes, the photoluminescence intensity of the silicon vacancy color center first increased and then decreased.

[0029] Preferably, the heating temperature in step (4) is 400-800° C., preferably 550-650° C.; the heating time is 1 minute to 24 hours, preferably 10 minutes to 4 hours, more preferably 30-90 minutes.

[0030] A third aspect of the present invention provides the use of diamond particles having silicon vacancy color centers in physically unclonable functional materials, wherein the physically unclonable functional material comprises: a single crystal silicon substrate and diamond particles having silicon vacancy color centers grown in situ thereon.

[0031] In a preferred embodiment of the present invention, the diamond particles having silicon vacancy color centers are grown on the single crystal silicon substrate by chemical vapor deposition. Preferably, the chemical vapor deposition method uses nanodiamonds treated with salt-assisted air oxidation as chemical vapor deposition seeds.

[0032] A fourth aspect of the present invention provides a physically unclonable functional tag, which includes the physically unclonable functional material based on diamond particles of the present invention or the physically unclonable functional material based on diamond particles prepared according to the preparation method of the present invention.

[0033] The physically unclonable functional material and preparation method thereof of the present invention have the following characteristics and beneficial effects:

[0034] (1) The preparation of diamond particles on silicon substrates is a random (non-deterministic) process, which is a key requirement for the manufacture of PUF tags. The developed diamond PUF shows excellent performance in terms of capacity, diversity, security, manufacturability, robustness and compatibility. The fabricated diamond-based anti-counterfeiting tags show superb stability under extreme conditions, including harsh chemical environments, high temperatures, mechanical wear and ultraviolet light irradiation. The multi-mode, dynamic encoding capabilities and excellent robustness of diamond PUFs indicate that they have great potential in realizing unbreakable anti-counterfeiting applications.

[0035] (2) Physically unclonable functions are produced during the chemical vapor deposition process, so they can be seamlessly integrated with modern microelectromechanical systems (MEMS) or nanoelectromechanical systems (NEMS) and mass-produced on wafers; in addition, the complexity and high cost of chemical vapor deposition equipment will also increase the difficulty of replicas appearing on the market.

[0036] (3) The flexible variation of CVD growth parameters (such as gas composition and flow rate, microwave power, pressure, growth time and temperature, diamond seed crystals and substrates) and wafer-scale production capabilities make large-scale commercial customization of diamond-PUF tags possible. In addition, the in-situ heterogeneous CVD growth of diamond particles on the substrate (rather than directly drop-coating / spin-coating pre-synthesized particles on the substrate as PUF tags) greatly ensures the bonding strength between the diamond particles and the silicon substrate, which further makes the diamond-PUF tag of the present invention as a whole have good stability.

[0037] (4) The high-quality silicon vacancy-containing diamond particles of the present invention have photoluminescence modulation properties (through air oxidation), which provides further security for the PUF tag.

[0038] (5) The present invention utilizes the photoluminescence intensity, scattering spectrum, morphological characteristics, and spatial positional relationships of diamond particles as the fingerprint information of the diamond PUF anti-counterfeiting label. Due to the extreme thermal, mechanical, chemical, and light stability of diamond materials, the highly robust label of the present invention can meet the requirements of many practical applications in various environments and has real commercial value in the vast anti-counterfeiting market, such as electronic components, pharmaceutical packaging, vehicles, and luxury goods.

[0039] BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Hereinafter, embodiments of the present invention will be described in detail with reference to the accompanying drawings, in which:

[0041] FIG1 shows the silicon vacancy structure and energy levels of the physically unclonable functional material based on diamond particles of the present invention;

[0042] FIG2 is a morphological structure characterization diagram of diamond particles prepared on a silicon wafer in Example 1;

[0043] FIG3 is a fluorescence emission spectrum of the diamond particles obtained in Example 1;

[0044] FIG4 is a scanning transmission electron microscope (STEM) image of the diamond particles of Example 1 and a corresponding electron energy loss spectroscopy (EELS) elemental distribution diagram;

[0045] FIG5 is a scanning electron microscope image (SEM) of the diamond particles of Example 1 and a dark field microscope image of the same area;

[0046] FIG6 is a detailed SEM image and corresponding scattering spectrum of five particles randomly selected from the area of ​​FIG5 ;

[0047] FIG7 shows a representative encoding result using the scattered signals of the diamond particles obtained in Example 1;

[0048] FIG8 is a representative encoding result of the silicon vacancy photoluminescence intensity of the diamond particles prepared in Example 3;

[0049] FIG9 is a confocal fluorescence microscope image of a 20 μm×20 μm area of ​​the diamond particles obtained in Example 3, which were oxidized in air at 600° C. for 15 minutes and repeated four times (total 60 minutes).

[0050] FIG10 is SEM images of the diamond particles obtained in Example 3 after being oxidized in air at 600° C. for 15, 30, 45, and 60 minutes;

[0051] FIG11 is a SEM image result of stability analysis of diamond particles in Example 3;

[0052] FIG12 is a confocal fluorescence microscope image of the stability analysis of the diamond particles in Example 3;

[0053] FIG13 is an SEM image of products with different diamond particle coverages obtained in Examples 2-5;

[0054] FIG14 is an encoding method based on the scattered light signal of diamond particles;

[0055] Figure 15 shows the readout process of a diamond-PUF tag using a 532nm green laser;

[0056] Figure 16 studies the effects of different measurement conditions (ambient light, exposure time, and laser power) on the SiV PL-based encoding results of the same diamond-PUF tag;

[0057] FIG17 shows the modulation process of SiV PL in diamond particles;

[0058] FIG18 shows the stability test results of the diamond-PUF anti-counterfeiting label;

[0059] FIG19 is a schematic diagram of a diamond-PUF-based authentication protocol;

[0060] FIG20 is a schematic diagram of an information encryption and decryption scheme based on diamond-PUF.

[0061] Best Mode for Carrying Out the Invention

[0062] The present invention will be further described below with reference to the following examples. The examples are merely illustrative and are not intended to limit the scope of the present invention in any way.

[0063] To facilitate understanding, some terms in the present invention are defined or explained below.

[0064] Uniformity

[0065] The uniformity can be calculated using the following formula:

[0066] Among them, R i is the i-th bit response from the n-bit key.

[0067] Similarity or similarity index

[0068] The similarity index (I) is used to detect the similarity between different PUFs and can be calculated using the following formula:

[0069] Where A is the number of pixels that are the same between the two PUFs, and B is the total number of pixels in the PUF.

[0070] Hamming distance

[0071] The Hamming distance between two keys is the minimum number of substitutions required to convert one key into another. The Hamming distance quantifies the uniqueness of a PUF and is the ability to distinguish one PUF from another. Furthermore, the Hamming distance can be used to quantify the reliability of a single PUF tag, examining its ability to generate consistent keys over multiple measurements. The Hamming distance is used to evaluate its uniqueness and reliability. The specific calculation formula is as follows:

[0072] Among them, R i and R j is the n-bit key of the i-th and j-th PUFs, and N is the total number of PUFs;

[0073] Where R0 is the original n-bit key of PUF, R iis the n-bit key of the same PUF generated by the i-th measurement among N measurements.

[0074] Example 1

[0075] (1) Salt-assisted air oxidation

[0076] 0.5 g of nanodiamond (HPHT, PolyQolor, China) with an average particle size of 50 nm was mixed with 2.5 g of sodium chloride (NaCl, 99.5%, Sigma-Aldrich) and heated at 500° C. for 1 hour in air.

[0077] (2) Preparation of chemical vapor deposition seed suspension

[0078] The resulting sample was dispersed in deionized water and sonicated for 1 hour, and the nanodiamonds were then purified three times with deionized water by centrifugation. The purified nanodiamonds were redispersed in deionized water and sonicated for 2 hours to obtain a well-dispersed nanodiamond seed suspension for chemical vapor deposition diamond growth, wherein the nanodiamond concentration was 1 mg / mL.

[0079] (3) Preparation of diamond particles on silicon wafers using chemical vapor deposition technology

[0080] A 2-inch silicon substrate was first treated with hydrogen plasma in a microwave plasma-assisted chemical vapor deposition (MPCVD) system (Seki 6350) for 10 minutes at a power of 1300 W, a chamber pressure of 35 Torr, and a hydrogen gas flow rate of 300 sccm. The prepared chemical vapor deposition diamond seed suspension was then spin-coated onto a standard single-crystal silicon substrate (spin coating parameters: 500 rpm, three drops of 20 μL of seed suspension added over 15 seconds, then the speed was increased to 4500 rpm, and the spin coating was continued for 110 seconds before drying). This was repeated five times. The diamond-seeded silicon substrate was then placed in an MPCVD system (Seki 6350) for the deposition and growth of diamond particles. The system was operated at a microwave power of 3400 W, a chamber pressure of 85 Torr, a growth temperature of 920°C, a hydrogen gas flow rate of 485 sccm, a methane (CH4) gas flow rate of 15 sccm, and a growth time of 80 minutes.

[0081] Example 2

[0082] Diamond particles were prepared on a silicon substrate in the same manner as in Example 1, except that the operation of spin coating the diamond seed suspension on the surface of the standard single crystal silicon substrate in step (3) was performed only once.

[0083] Example 3

[0084] Diamond particles were prepared on a silicon substrate in the same manner as in Example 1, except that the operation of spin coating the diamond seed suspension on the surface of the standard single crystal silicon substrate in step (3) was repeated 10 times.

[0085] Example 4

[0086] Diamond particles were prepared on a silicon substrate in the same manner as in Example 1, except that the operation of spin coating the diamond seed suspension on the surface of the standard single crystal silicon substrate in step (3) was repeated 20 times.

[0087] Example 5

[0088] Diamond particles were prepared on a silicon substrate in the same manner as in Example 1, except that the operation of spin coating the diamond seed suspension on the surface of the standard single crystal silicon substrate in step (3) was repeated 25 times.

[0089] Example 6

[0090] Representative encoding process using the scattered signals of diamond particles

[0091] An optical microscope was used to capture an image of the diamond particles obtained in Example 1 under bright field conditions. A 200 μm × 200 μm area was randomly selected and converted into a black and white image using image processing software (e.g., Photoshop). The corresponding black and white image was then encoded into a 50 pixel × 50 pixel two-dimensional binary encoding matrix based on the principle of black (0) and white (1). The result is shown in FIG7 .

[0092] Example 7

[0093] Representative encoding process of silicon vacancy photoluminescence intensity using diamond microparticles

[0094] A confocal fluorescence microscope was used to capture a photoluminescence image of the diamond particles produced in Example 3 within a 100 μm × 100 μm area (100 pixels × 100 pixels). The photoluminescence intensity data (counts per second) for each 2-pixel × 2-pixel (or 4-pixel × 4-pixel) image was then combined into the photoluminescence intensity data (counts per second) for a single pixel, creating a new 50-pixel × 50-pixel (or 25-pixel × 25-pixel) image. The photoluminescence intensity data (counts per second) for each pixel in the newly composed image was then divided into 4 groups (quaternary encoding), 10 groups (decimal encoding), or 16 groups (hexadecimal encoding) based on the order of intensity. The results are shown in Figure 8.

[0095] Example 8

[0096] Air Oxidation-Photoluminescence Modulation of Diamond Microparticles Grown by Chemical Vapor Deposition

[0097] The diamond particles prepared in Example 3 were heated in air at 600° C. for 15 minutes, and the heating process was repeated 4 times, thereby modulating the photoluminescence intensity of the silicon vacancy color centers in the diamond particles.

[0098] Morphology and performance characterization methods

[0099] The morphology of the diamond particles was analyzed using a scanning electron microscope (SEM, Hitachi S-4800, Japan). Elemental composition was analyzed using electron energy loss spectroscopy (EELS) on a scanning transmission electron microscope (STEM, JEM-2100F). Crystallinity was analyzed using X-ray diffraction (XRD, D8 Advance, Bruker). Optical characterization of the samples was performed using a dark-field microscope equipped with a spectrometer built in the laboratory. Optical characterization of the samples was performed using a confocal fluorescence microscope equipped with a spectrometer built in the laboratory.

[0100] Diamond particle stability test method

[0101] Chemical stability: The prepared diamond particles were immersed in supersaturated sodium chloride (NaCl), 1 mol / L hydrochloric acid (HCl), and 1 mol / L sodium hydroxide (NaOH) solutions for 48 hours, and then rinsed with clean water.

[0102] Thermal stability: Diamond particles were heated from room temperature to 400°C in air and kept at this temperature for 48 hours.

[0103] Mechanical stability: Diamond particles were mixed with sand, physically rubbed for 30 minutes, and then cleaned with water under ultrasound (1 hour).

[0104] Light stability: The diamond particles were exposed to ultraviolet light (365 nm) for 2 hours.

[0105] After each of the above stabilization treatments, the functionality of the diamond particles was characterized.

[0106] Results and Analysis

[0107] (1) Figure 2 shows the morphological characterization results of the diamond particles prepared on the silicon wafer in Example 1, specifically including: (a) a photograph of the silicon wafer covered with diamond particles; (b) the corresponding SEM image, (c) a 45° SEM image, (d) a cross-sectional SEM image, (e) a size distribution of the grown diamond particles calculated based on the SEM image (with an average size of approximately 1.32 μm), (f) a Raman spectrum, and (g) an X-ray diffraction spectrum.

[0108] Raman spectroscopy and X-ray diffraction patterns demonstrate the pure crystalline nature of the grown diamond particles. Furthermore, etching the silicon substrate during chemical vapor deposition produces a large number of doped silicon atoms, which can enter the diamond lattice to form silicon vacancy color centers, exhibiting superior fluorescence properties compared to silicon vacancy color centers generated by ion implantation.

[0109] (2) Room-temperature photoluminescence properties of diamond particles grown by chemical vapor deposition. Ideal fluorescent anti-counterfeiting labels require materials with strong fluorescence (photoluminescence) intensity to ensure high fluorescence brightness. Figure 3 shows that the diamond particles produced in Example 1 exhibit a narrow fluorescence emission peak at approximately 737 nm (excitation light is 532 nm).

[0110] FIG4 shows (a) a STEM image and (b) a corresponding EELS element distribution image of the diamond particles of Example 1, indicating that a large number of doped silicon atoms are uniformly present in the diamond particles.

[0111] (III) Figure 5 shows (a) an SEM image of the diamond particles of Example 1 and (b) a dark-field microscopy image of the same area. Five randomly selected particles, labeled 1, 2, 3, 4, and 5, are also characterized in detail. Figure 5 shows the random distribution of the diamond particles, with bright scattering points. Figure 6 shows (a) the specific morphology and (b) the corresponding scattering spectra of five randomly selected particles, 1, 2, 3, 4, and 5, from the area of ​​Figure 4. The scattering peaks are primarily distributed between 450 and 800 nm, with each spectrum having a unique peak position, intensity, and line width. Furthermore, the SEM images show that the morphology of the particles is distinct, meaning that each diamond particle's morphology and scattering spectrum are unique within its class. Therefore, the scattering spectra of the diamond particles, as well as their morphological characteristics and spatial positional relationships, can be used as fingerprint information for the diamond PUF. This is one of the most important factors to consider for the practical application of convenient, rapid, and inexpensive detection or readout of diamond optical tags. By using a portable readout device (e.g., a smartphone camera), the scattering point pattern and scattering intensity of the diamond microparticle PUF tag can be simultaneously acquired in one image, enabling flexible detection of the optical tag.

[0112] (IV) Figure 7 shows a representative encoding process using the scattered signals of diamond particles. First, an optical microscope is used to capture an image of the diamond particles obtained in Example 1 under bright field conditions (a), and a 200μm×200μm area is randomly selected and converted into a (b) black and white image using image processing software (such as Photoshop). The corresponding black and white image is then encoded into a 50 pixel×50 pixel two-dimensional binary encoding matrix (c) according to the principle of black (0) and white (1). The Hamming distance (d) of the corresponding encoding matrix proves that the obtained two-dimensional binary encoding matrix has good randomness. The encoding results of 100 random areas show that the obtained diamond particle PUF tag has good (e) uniformity, low (f) similarity index and good (g) Hamming distance between tags.

[0113] (V) Figure 8 shows a representative encoding process using the photoluminescence intensity of silicon vacancies in diamond particles. First, a photoluminescence image (a) of a 100 μm × 100 μm area (100 pixels × 100 pixels) of the diamond particles produced in Example 3 was captured using a confocal fluorescence microscope. The distribution graph (b) and cumulative curve (c) of the photoluminescence intensity (counts per second) over the corresponding measurement area demonstrate that the photoluminescence intensity of silicon vacancies in the resulting diamond particles has a wide distribution range, making it well-suited for multi-bit encoding.

[0114] Specifically, the photoluminescence intensity data (counts per second) for each 2×2 pixel (or 4×4 pixel) of the measured photoluminescence image (a) are combined into the photoluminescence intensity data (counts per second) for a single pixel, forming a new 50×50 pixel (or 25×25 pixel) image. The photoluminescence intensity data (counts per second) for each pixel in the newly formed image are then divided into four groups based on intensity and encoded in 4th order (d), 10 groups in 10th order (e), or 16 groups in 16th order (f). In (d), (e), and (f), the top image shows the 25×25 pixel encoding result, and the bottom image shows the 25×25 pixel encoding result. The left image shows the specific encoding matrix, the middle image shows the similarity index (10 tags, each measured twice), and the right image shows the inter- and intra-class Hamming distances for the 10 tags. These results demonstrate that the silicon vacancy photoluminescence intensity of diamond particles can facilitate the development of multidimensional PUF tags with large encoding capacity.

[0115] (VI) Figure 9 shows the photoluminescence image of a 20 μm × 20 μm area of ​​diamond particles produced in Example 3, obtained by oxidizing them in air at 600°C for 15 minutes, repeated four times (a total of 60 minutes). It can be seen that the photoluminescence intensity of the silicon vacancy color center in the diamond particle changes with oxidation. Furthermore, the air-oxidized diamond particle exhibits no significant morphological changes (Figure 10). Therefore, this photoluminescence modulation property of the silicon vacancy color center provides the diamond tag with an "internal" security key.

[0116] (VII) Stability analysis results are shown in Figure 11, including: (a) SEM image of untreated raw diamond particles; (b) Thermal stability: SEM image of diamond particles after heating at 400°C for 48 hours; (c) Mechanical stability: SEM image of diamond particles after rubbing with sand and washing; (d) Chemical stability: SEM image of diamond particles after immersion in supersaturated sodium chloride (NaCl), 1 mol / L hydrochloric acid (HCl), and 1 mol / L sodium hydroxide (NaOH) solutions for 48 hours. In addition, confocal fluorescence images of diamond particles before and after a series of treatments with salt (NaCl), acid (HCl), base (NaOH), high temperature (400°C), mechanical force, and ultraviolet light (365nm) were also tested (Figure 12). The results show that these treatments did not cause any damage to the photoluminescence properties of the diamond particles, and encoding was still possible. Therefore, the diamond PUF of the present invention has excellent robustness to salt (NaCl), acid (HCl), base (NaOH), high temperature (400°C), mechanical force, and ultraviolet light.

[0117] (8) In Examples 2-5, by adjusting the growth parameters (the number of repetitions of spin-coating the diamond seed suspension onto the surface of a standard single-crystal silicon substrate), the grown diamond particles covered 0.146% to 100.00% of the silicon wafer (SEM images of Examples 2-5 are shown in Figures (a)-(d) of Figure 13, respectively). This further provides significant room for adjusting the encoding capabilities of the diamond PUF tag of the present invention.

[0118] Static coding based on scattered light signals from diamond particles

[0119] In practical anti-counterfeiting applications, diamond-PUF tags should be able to be detected and read quickly, cheaply and conveniently. Figure 14 shows the encoding method based on the scattered light signal of diamond particles, where: (a) includes (i) an authentication device consisting of a portable microscope and a smartphone; (ii) an optical image of the diamond-PUF tag taken by the portable microscope; (iii) a dark field microscope image of the dotted area in Figure (ii); (iv) a SEM image of the dotted area in Figure (ii); (b) a black and white image converted from the 200 μm × 200 μm dotted area in Figures (a-ii); (c) the corresponding binary encoding based on the dark (0) and light (1) levels of each pixel in Figure (b). matrix, with a resolution of 50 pixels × 50 pixels; (d) the distribution (normalized) results of the similarity index and (e) the Hamming distance, obtained by analyzing the keys generated by 100 tags; (f) the scattering spectra and corresponding SEM images of three random diamond particles in the selected area (particles 1, 2, and 3 in Figures (a-iii) and (a-iv)); (g) the numerically calculated scattering spectra of diamond particles with different shapes (~1 μm), (h) sizes (shape-1: cuboctahedron), (j) substrates (~1.5 μm), and (k) crystallinity (bicrystal and tricrystal).

[0120] Due to the high refractive index of diamond material (approximately 2.4), the fabricated diamond-PUF tag can be easily read by a portable reader device, such as a smartphone-based portable microscope, as shown in Figures 14(a-ii). This enables the diamond-PUF tag to be easily detected without the need for complex instrumentation. Figures 14(a-ii) show typical optical images of a diamond-PUF tag captured by a portable device. To generate quantitative metrics commonly used in PUF research, the optical image is converted into a security key. To this end, the image is binarized and downscaled to 50 pixels by 50 pixels (Figures 14(b) and (c)). In Figure 14(c), white pixels correspond to bright areas, which are light-scattering signals from the diamond particles on the PUF tag. Furthermore, the Hamming distance (normalized), which measures the minimum number of permutations between different rows within the corresponding binary encoding matrix, is calculated. The calculated result conforms to the normal distribution of the generated key. This binary image is then used to generate a 2500-bit security key consisting of 1 bits and 0 bits. This procedure was repeated for 100 samples to generate 100 different security keys. For each of these keys, the uniformity, similarity index (the percentage of identical pixels between the two PUFs, Figure 14(d)), and Hamming distance (Figure 14(e)) were calculated. The results show that the arithmetic means of the uniformity (0.4996), similarity index (49.9978%), and Hamming distance (0.5000) are all close to the ideal values ​​(i.e., 0.5, 50%, and 0.5), demonstrating that the diamond PUFs of this invention exhibit excellent uniformity, uniqueness, and randomness.

[0121] Typically, scattering patterns are insufficient for applications requiring advanced security because they are relatively easy to replicate using 3D nanoprinting or other assembly techniques. To enhance the security of PUF tags, the scattering spectra of diamond particles can be further exploited. The scattering spectra of diamond particles have been shown to be extremely sensitive to topological structure, such as size, shape, and crystallinity. Therefore, accurately replicating them with identical spectra is unrealistic. Figures 14 (a-iii) and (a-iv) show typical dark-field microscopy and SEM images of a random region of a diamond-PUF tag. Diamond particles are randomly distributed, appearing as bright scattering points. The detailed shapes and corresponding scattering spectra of some particles were measured (Figure 14 (f)). The scattering peaks are primarily between 450 and 800 nanometers, and each spectrum has its own unique peak position, intensity, and spectral linewidth. Furthermore, according to SEM images, no particle has the same shape; that is, each diamond microparticle is unique. Therefore, the scattering spectra of diamond particles, along with their shape characteristics and spatial position, can serve as the fingerprint of the diamond PUF. To explore the potential of modulating scattering spectra, detailed numerical simulations were performed on the scattering spectra of diamond particles with varying shapes (Figure 14(g)), sizes (Figure 14(h)), substrates (Figure 14(j)), and crystallinity (Figure 14(k)). The results demonstrate the potential of using diamond scattering spectra as an advanced anti-counterfeiting method. Furthermore, due to the high refractive index of diamond, even when covered by protective layers such as SiO2 or Al2O3, it still produces a significant light scattering signal for reading.

[0122] Static coding based on SiV PL intensity

[0123] In addition to using the light scattering signal of diamond particles as anti-counterfeiting tags, advanced encoding can also be achieved by utilizing the PL signal of fluorescent color centers (such as SiV color centers) embedded in the diamond lattice. Diamond particles with a large number of doped Si atoms exhibit a significant SiV signal. The SiV PL intensity of each pixel in the fluorescence image is used to encode the diamond-PUF tag.

[0124] Figure 15 shows the readout process of a diamond-PUF tag using a 532 nm green laser, where: (a) is a schematic diagram of the readout process of a diamond-PUF tag; (b) is a confocal fluorescence image of a diamond-PUF tag with an area of ​​100 μm × 100 μm; (c) is a cumulative curve of the PL intensity (photon counts: cps) of the measurement area shown in (b); (d)-(f) show the digitized quaternary, decimal, and hexadecimal PL encoding results of the measurement area in (b) at a resolution of 50 pixels × 50 pixels. Pairwise comparisons of 25 PUF tags with the quaternary, decimal, and hexadecimal encoding of the PL intensity level of each pixel are shown next to the corresponding encoding matrix, with the x-axis and y-axis representing the first and second measurements of the tag, respectively, and the color bar showing the similarity index; (g) is the corresponding inter-Hamming distance and intra-Hamming distance (normalized) of the quaternary, decimal, and hexadecimal keys generated from the 25 tags. Figure 16 shows the impact of different measurement conditions (such as ambient light, exposure time, and laser power) on the SiV PL-based encoding results of the same diamond-PUF tag. (a) shows a confocal fluorescence image of the same diamond-PUF tag under standard measurement conditions (no ambient light, 5 milliseconds exposure time, and 0.5 milliwatt laser power); (b) shows confocal fluorescence images of the same diamond-PUF tag with and without ambient light; (c) shows confocal fluorescence images of the same diamond-PUF tag with 1.5 milliseconds and 10 milliseconds exposure times; (d) shows confocal fluorescence images of the same diamond-PUF tag with 0.1 milliwatt and 0.5 milliwatt laser power; and (e) shows the similarity (%) analysis results of the quaternary keys generated by the same diamond-PUF tag under different measurement conditions. During the verification process, all conditions except the tested condition remained unchanged. For example, when testing the impact of ambient light, the exposure time and laser power remained unchanged (5 milliseconds and 0.5 milliwatt).

[0125] As shown in Figure 15(a), under 532 nm laser irradiation, the diamond-PUF tag produces a unique optical fingerprint, namely, a confocal fluorescence image of an area of ​​100 μm × 100 μm (shown in Figure 15(b)), which is impossible to imitate. Due to the high diversity of SiV centers within each diamond particle, advanced (e.g., quaternary, decimal, and hexadecimal) encoding of the PL intensity of each pixel can be achieved. Figure 15(c) shows the principles of quaternary, decimal, and hexadecimal encoding using the cumulative curve of the PL intensity (photon counts: cps) of the measurement area in Figure 15(b), enabling the generated key to be uniformly distributed. Figures 15(d)-(f) show the quaternary, decimal, and hexadecimal PL encoding results of the measurement area in Figure 15(b). As can be seen, the two measurement results for the same tag are highly similar, making it easy to distinguish between genuine and counterfeit tags. The distribution of the normalized inter-Hamming distance and intra-Hamming distance (i.e., Hamming distance divided by key length) for the generated quaternary, decimal, and hexadecimal keys is shown in Figure 15(g). These results demonstrate the ability of the diamond PUF system of the present invention to generate diverse codes. Furthermore, when capturing PL images, measurement conditions (such as ambient light, exposure time, and laser power) do not affect the final keys generated by the same diamond PUF tag using this PL-based encoding process (Figure 16).

[0126] Dynamic encoding of SiV PL intensity modulation based on air oxidation

[0127] Modulation of SiV PL in diamond has been demonstrated by several treatments, including air oxidation and vacuum annealing. Such dynamic and controllable SiV PL systems have the potential to become candidates for developing advanced time-dependent encoding methods.

[0128] Figure 17 shows the modulation process of SiV PL in diamond particles, where: (a) is a confocal fluorescence image of a diamond-PUF tag with an area of ​​100 μm × 100 μm; (b) is a 20 μm × 20 μm dashed area in (a) at three different times (t0, t x and t y ); (c) is the confocal fluorescence image of the 10 random diamond particles circled in (b) at three different times (t0, t x and t y ) is the PL intensity of the image; (d) is the digitized result of the decimal encoding of the area shown in (b), based on the PL intensity of each pixel, with a resolution of 25 pixels × 25 pixels.

[0129] As shown in Figure 17(a), air oxidation (temperature: 600°C, time interval: 15 minutes) modulated the SiV PL in the produced diamond particles. Furthermore, the selected diamond particles did not show any morphological changes after four cycles of air oxidation. The 20 μm × 20 μm dashed area in Figure 17(a) was oxidized at three different times: t0, t x (30 minutes) and t y Confocal fluorescence imaging of the PL counts measured at different times (60 minutes) reveals significant variation in the measured PL counts for each particle (Figure 17(b)), with variations in PL intensity varying from particle to particle (Figure 17(c)). Consequently, confocal fluorescence images measured at different times (Figure 17(b)) can be digitized into distinct codes (Figure 17(d)) ​​that lack strong correlation. Analysis of the similarity index (Figure 17(e)) and Hamming distance (Figure 17(f)) of decimal keys generated at the same and different times demonstrates the successful implementation of time-correlated encoding based on PL intensity modulation by air oxidation. For diamond-PUF tags at the same time, the average similarity index and Hamming distance are 72.80% and 0.27, with standard deviations of 9.38% and 0.09, respectively. When they are obtained from different times, the average similarity index and Hamming distance are 25.69% and 0.743, with standard deviations of 1.24% and 0.01, respectively. Therefore, air oxidation of the diamond PUF results in an overall change in the SiV PL intensity of each of its particles, in response to the construction of a dynamic diamond PUF key. In this case, a new key is generated after each round of air oxidation due to the random modulation of the SiV centers in the diamond during the oxidation process. This non-deterministic, time-varying encoding strategy allows the encoding key of the same PUF tag to be artificially changed when the original tag is exposed to malicious attacks and the risk of being copied, a desirable feature for the design and manufacture of anti-counterfeiting materials with advanced security.

[0130] Furthermore, the stacking pattern of diamond particles on the substrate can be dynamically controlled by air oxidation. The multi-generational microstructure of diamond particles can also serve as a PUF pattern to promote time-varying encoding. Therefore, end users of the diamond-PUF anti-counterfeiting system (Figure 17(g)) can potentially use the strategy developed in this invention to build their own database for higher security.

[0131] Stability of Diamond-PUF Anti-Counterfeiting Labels

[0132] These experimental results demonstrate the excellent performance of diamond microparticles on silicon substrates in generating PUFs. For practical applications, the chemical, mechanical, thermal, and light stability of anti-counterfeiting labels are also crucial. Therefore, the stability of diamond PUF labels to alkali (NaOH), acid (HCl), salt (NaCl), mechanical forces, high temperatures (400°C), and ultraviolet light was evaluated.

[0133] Figure 18 shows the stability test results of the diamond-PUF anti-counterfeiting label, where: (a) is an optical microscope image of the same area of ​​the diamond-PUF label before and after a series of extreme treatments: (1) soaked in 1 mol / L NaOH for 24 hours; (2) soaked in 1 mol / L HCl for 24 hours; (3) ground with NaCl particles and soaked in supersaturated NaCl for 24 hours, and then washed with water under ultrasonic treatment (1 hour); (4) heated at 400°C for 24 hours; (5) exposed to UV light for 2 hours; (b) is the similarity of the binary keys generated before and after treatment, with the x-axis and y-axis representing the first and second measurements of the label, respectively, and the color bar shows the similarity index; (c) is the Hamming distance distribution (normalized) of the binary keys generated by ten diamond-PUF labels before and after treatment; (d) is a confocal fluorescence image of the same area on the diamond-PUF label before and after a series of extreme treatments; (e) is the photostability test of SiV color centers in diamond microparticles (2 hours).

[0134] The results show that after a series of extreme treatments, the optical response and morphology of the diamond particles remain unchanged (Figure 18(a) and (d)), demonstrating their excellent stability in diverse extreme application scenarios. Furthermore, similarity analysis (Figure 18(b)) and Hamming distance analysis (Figure 18(c)) of the binary keys generated before and after treatment confirm that the encoding capability of the diamond particles is unaffected by the extreme treatments. Furthermore, the photostability of the diamond particles was examined by irradiating the SiV color centers with a 532-nanometer laser for two hours. During the measurement, the particles exhibited excellent photostability deviation of less than 1.19%. These results demonstrate that the proposed diamond-PUF tag possesses excellent chemical, mechanical, thermal, and photostability.

[0135] Diamond-PUF-based authentication protocol

[0136] In some embodiments of the present invention, authentication can be performed using the materials of the present invention. Figure 19 shows a schematic diagram of an authentication method, wherein the authentication process can be divided into two steps, including registration and verification steps.

[0137] (1) During the enrollment phase, the input challenge signal (C1) is projected onto the diamond-PUF, generating a corresponding response signal (R1), which is then converted into a secret key (K1). The challenge-response pair consisting of C1 and the enrollment information of K1 is then stored in a cloud database.

[0138] (2) In the verification phase, the verifier randomly selects C1 from the cloud database to challenge a PUF to be authenticated and obtains a check code K1'. The check code is uploaded to the data cloud and the similarity index (I) or Hamming distance between K1 and K1' is compared. If I (K1,K1') If the value is greater than the preset threshold, the verification is true; otherwise, the verification result is false.

[0139] Diamond-PUF-based information encryption and decryption scheme

[0140] Secure communication between two parties is crucial for everyday information security. In some embodiments of the present invention, the materials of the present invention can be used to encrypt secure information. Figure 20 shows a schematic diagram of a method for information encryption and decryption, where (a) illustrates the generation of encryption and decryption keys; (b) illustrates the encryption and decryption process.

[0141] First, two unique diamond-PUFs (A and B) are used to generate a random key (K A and K B ), which belong to the encryption party and the decryption party respectively. The two keys are then mixed and stored in a public database (K A ⊕K B ). In the information encryption stage, the diamond-PUF key K A Used to encrypt a message (M) to generate a ciphertext (M⊕K A ), and then transmit it to the decryption end through a public channel. During the information decryption process, the diamond-PUF key K is used B , by combining the public database with the key K B Mix to decrypt the ciphertext, that is, K B ⊕(K A ⊕K B )⊕(M⊕K A ) = M. Due to the uniqueness and non-replicability of the diamond-PUF tag, no key sharing and storage is required during the encryption and decryption process, ensuring efficient and secure information communication.

[0142] The above embodiments are merely preferred embodiments of the present invention and do not limit the present invention in any way. Any equivalent substitution, modification, or other variation of the technical solution and technical content disclosed in the present invention made by any person skilled in the art without departing from the scope of the present invention does not depart from the technical solution of the present invention and remains within the scope of protection of the present invention.

Claims

1. A physically unclonable functional material based on diamond particles, comprising: A single crystal silicon substrate and diamond particles with silicon vacancy color centers grown in situ thereon.

2. The physically unclonable functional material according to claim 1, wherein: The diamond particles having silicon vacancy color centers are grown on the single crystal silicon substrate by chemical vapor deposition. Preferably, the chemical vapor deposition method uses nanodiamonds treated with salt-assisted air oxidation as seeds.

3. The physically unclonable functional material according to claim 2, wherein: The salt-assisted air oxidation treatment includes mixing nanodiamonds with soluble salts and heating them in air at 200-900° C. for 1 minute to 24 hours, wherein the soluble salt is preferably sodium chloride; preferably, the mass ratio of the nanodiamonds to the soluble salt is 1:0.1-10.

4. The physically unclonable functional material according to claim 1, wherein: The particle size of the diamond particles is 50 to 100,000 nm, preferably 100 to 10,000 nm.

5. The physically unclonable functional material according to claim 2, wherein: The particle size of the nanodiamond used as a chemical vapor deposition seed is 1 to 500 nm, preferably 5 to 100 nm.

6. The physically unclonable functional material according to claim 1, wherein: The substrate is a single crystal silicon substrate. Preferably, the coverage of the diamond particles on the surface of the single crystal silicon substrate may be 0.1% to 100%, preferably 10% to 50%.

7. A method for preparing a physically unclonable functional material based on diamond particles, the method comprising: (1) salt-assisted air oxidation treatment of nanodiamonds; (2) preparing the treated nanodiamond into a seed suspension; (3) Applying the seed crystal suspension to the surface of a single crystal silicon substrate to form seed crystals, and then growing diamond particles with silicon vacancy color centers by chemical vapor deposition.

8. The preparation method according to claim 7, wherein The salt-assisted air oxidation treatment includes mixing nanodiamonds with a soluble salt and heating them in air at 200-900°C for 1 minute to 24 hours, wherein the soluble salt is preferably sodium chloride; preferably, the mass ratio of the nanodiamonds to the soluble salt is 1:0.1-10; preferably, the seed suspension uses dimethyl sulfoxide, anhydrous ethanol, acetone, water or a mixture thereof as a dispersion solvent.

9. The preparation method according to claim 7, wherein The step (3) includes treating the single crystal silicon substrate with hydrogen plasma before growing diamond particles. The preferred treatment conditions are: power of 100 to 2000 W, chamber pressure of 0.1 to 100 torr, hydrogen gas flow rate of 5 to 1000 sccm, and treatment time of 1 to 60 minutes.

10. The preparation method according to claim 7, wherein The chemical vapor deposition growth conditions in step (3) include: spin-coating a seed suspension onto a pretreated silicon substrate surface and repeating this process 1 to 30 times; then placing the silicon substrate spin-coated with diamond seeds into a chemical vapor deposition device to deposit and grow diamond particles; preferably, the microwave power of the device is 500 to 5000 W, the chamber pressure is 0.1 to 100 torr, the growth temperature is 400 to 1000° C., the hydrogen gas flow rate is 100 to 1000 sccm, the methane gas flow rate is 1 to 100 sccm, and the growth time is 10 to 120 minutes.

11. The preparation method according to claim 7, wherein The preparation method further comprises step (4): heating the generated diamond particles in air, preferably at a heating temperature of 400 to 800° C., more preferably 550 to 650° C.; preferably for a heating time of 1 minute to 24 hours, more preferably 10 minutes to 4 hours, and most preferably 30 to 90 minutes.

12. Use of diamond particles having silicon vacancy color centers as physically unclonable functional materials, wherein the physically unclonable functional materials comprise: A single crystal silicon substrate and diamond particles with silicon vacancy color centers grown in situ thereon.

13. The use according to claim 12, wherein: The diamond particles having silicon vacancy color centers are grown on the single crystal silicon substrate by chemical vapor deposition. Preferably, the chemical vapor deposition method uses nanodiamonds treated with salt-assisted air oxidation as seeds.

14. A physically unclonable functional tag, comprising the physically unclonable functional material based on diamond particles according to any one of claims 1 to 6 or the physically unclonable functional material based on diamond particles prepared according to the preparation method according to any one of claims 7 to 11.

Citation Information

Patent Citations

  • Single granule layer nanometer diamond film with strong Si-V luminescence, and production method thereof

    CN104831253A

  • Ultra-small-grain-size nano diamond film with SiV light emitting effect and preparation of Ultra-small-grain-size nano diamond film

    CN106498363A

  • Nano-diamond-based anti-counterfeiting method, corresponding medicine, anti-counterfeiting ink and application thereof

    CN108918485A

  • Preparation method of high-brightness silicon vacancy color centers in nano-diamond

    CN111099586A

Cited By

  • Physical unclonable anti-counterfeiting structure based on bionic nanostructure and application

    CN120071748A